2013
DOI: 10.3791/50667
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Respiratory Burst Response as an Indicator of Innate Immune Health in Zebrafish

Abstract: The phagocyte respiratory burst is part of the innate immune response to pathogen infection and involves the production of reactive oxygen species (ROS). ROS are toxic and function to kill phagocytized microorganisms. In vivo quantification of phagocyte-derived ROS provides information regarding an organism's ability to mount a robust innate immune response. Here we describe a protocol to quantify and compare ROS in whole zebrafish embryos upon chemical induction of the phagocyte respiratory burst. This method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…We then tested the ability of phagocytes to mount a respiratory burst response in vivo. A fluorescence assay to quantify the respiratory burst in zebrafish embryos has been previously described (31,32), in which PMA is used to activate protein kinase C, resulting in ROS production in phagocytes via NAPDH oxidase. At 48 hpf, the respiratory burst potentials of controls and sod2 morphants were similar (Fig.…”
Section: Sod2 Is Upregulated In Response To Lps In Mammalian Macrophamentioning
confidence: 99%
“…We then tested the ability of phagocytes to mount a respiratory burst response in vivo. A fluorescence assay to quantify the respiratory burst in zebrafish embryos has been previously described (31,32), in which PMA is used to activate protein kinase C, resulting in ROS production in phagocytes via NAPDH oxidase. At 48 hpf, the respiratory burst potentials of controls and sod2 morphants were similar (Fig.…”
Section: Sod2 Is Upregulated In Response To Lps In Mammalian Macrophamentioning
confidence: 99%
“…In a similar study, enhanced levels of respiratory burst activity were found in Nile tilapia fed with diet containing Se nanoparticles (Dawood et al, 2020). As a critical component of the innate immune response, phagocyte respiratory burst generates reactive oxygen species that kill invading microorganisms (Goody et al, 2013).…”
Section: Lysozyme and Respiratory Burst Activitiesmentioning
confidence: 72%
“…2020). As a critical component of the innate immune response, phagocyte respiratory burst generates reactive oxygen species that kill invading microorganisms (Goody et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of ROS production following a respiratory burst response is indicative of the intensity of the immune response and overall health of the organism. A method to assay the respiratory burst response was developed for zebrafish embryos and adult tissues (134)(135)(136). This assay measures production of H 2 O 2 in response to phorbol myristate acetate (PMA) by detecting the oxidation of dihydrodichlorofluorescein (H 2 DCF) FIGURE 2 | ROS Signaling in Response to Virus Infection.…”
Section: Respiratory Burst Responsementioning
confidence: 99%